Global clinicoepidemiological pattern of childhood vitiligo: a systematic review and meta-analysis - Saeedeh Farajzadeh; Maryam Khalili; Majid Mirmohammadkhani; Fatemeh Paknazar; Fereshte Rastegarnasab; Bahareh Abtahi-Naeini (BMJ Publishing Group, 2023)
Background Childhood vitiligo differs from adult vitiligo in many aspects. To the best of the authors' knowledge, there is no systematic review of different clinicoepidemiological patterns of vitiligo in children. This study aimed to review the characteristics of vitiligo among the paediatric population.Methods In June 2022, a comprehensive search was conducted using MeSh-based keywords on online databases including PubMed, Scopus and Web of Sciences. The papers were assessed, and the eligible articles were selected. The selection of articles followed three distinct steps. The extracted clinicoepidemiological data were then imported into the STATA software for meta-analysis.Results The meta-analysis of 17 studies with 4365 subjects yielded 2475 women (estimated=56.8%, 95% CI 54.45 to 59.22). The female-to-male ratio was determined to be 1.3:1. Meta-regression demonstrated a significant relationship between continents and gender (p=0.03). The most prevalent types of non-segmental vitiligo were vulgaris (42.49%), focal (27.21%) and acrofacial (17.8%). The pooled ratio of non-segmental to segmental was 4.6:1. The highest and lowest ratios were found in Africa with one study (estimated=11.56%, 95% CI −0.98 to 24.10) and America with two studies (estimated=3.02%, 95% CI 1.54 to 4.50), respectively. Using meta-regression, the relationship between continents and vitiligo type was found to be insignificant (p=0.47). Positive family history was recorded in 657 patients (estimated = 16.88%, 95% CI 13.37 to 20.39). Positive family history varied by country of study from 13.91% (Asia with 11 studies) to 27.01% (Europe with two studies) (p=0.11). Kobner phenomena and leukotrichia were noted in 687 (25.47%) and 461 (18.52%) patients, respectively.Conclusion The review indicated that childhood vitiligo is more prevalent in women. Non-segmental forms of childhood vitiligo were the most common, including vulgaris, focal and acrofacial. The clinicoepidemiological pattern of childhood vitiligo is variable in diﬀerent geographic areas.